Alkaloids as Promising Agents for the Management of Insulin Resistance: A Review - Amssayef, Ayoub; Eddouks, Mohamed (Current Pharmaceutical Design, 2023)
Background: Insulin resistance is one of the main factors that lead to the development of type 2 diabetes mellitus (T2DM). The effect of alkaloids on insulin resistance has been extensively examined according to multiple scientific researches. Objective: In this work, we aimed to summarize the interesting results from preclinical and clinical studies that assessed the effects of natural alkaloids (berberine, nigelladine A, piperine, trigonelline, capsaicin, nuciferine, evodiamine, mahanine, and magnoflorine) on impaired insulin sensitivity and worsened insulin resistance, which play a pivotal role in the pathogenesis of type 2 diabetes. Methods: In the current review, PubMed, ScienceDirect, Springer, and Google Scholar databases were used. The inclusion criteria were based on the following keywords and phrases: insulin sensitivity, insulin resistance, alkaloids and insulin resistance, alkaloids and type 2 diabetes, mechanisms of action, and alkaloids. Results: The outcomes reported in this review demonstrated that the selected alkaloids increased insulin sensitivity and reduced insulin resistance in vitro and in vivo evidence, as well as in clinical trials, through improving insulin-signaling transduction mainly in hepatocytes, myocytes, and adipocytes, both at cellular and molecular levels. Insulin signaling components (InsR, IRS-1, PI3K, Akt, etc.), protein kinases and phosphatases, receptors, ion channels, cytokines, adipokines, and microRNAs, are influenced by alkaloids at transcriptional and translational levels, also in terms of function (activity and/or phosphorylation). Multiple perturbations associated with insulin resistance, such as ectopic lipid accumulation, inflammation, ER stress, oxidative stress, mitochondrial dysfunction, gut microbiota dysbiosis, and β-cell failure, are reversed after treatment with alkaloids. Furthermore, various indices and tests are employed to assess insulin resistance, including the Matsuda index, insulin sensitivity index (ISI), oral glucose tolerance test (OGTT), and insulin tolerance test (ITT), which are all enhanced by alkaloids. These improvements extend to fasting blood glucose, fasting insulin, and HbA1c levels as well. Additionally, the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) and the Homeostasis Model Assessment of β-cell function (HOMA-β) are recognized as robust markers of insulin sensitivity and β-cell function, and it is noteworthy that alkaloids also lead to improvements in these two markers. Conclusion: Based on the findings of the current review, alkaloids may serve as both preventive and curative agents for metabolic disorders, specifically type 2 diabetes. Nonetheless, there is an urgent need for additional clinical trials to explore the potential benefits of alkaloids in both healthy individuals and those with type 2 diabetes. Additionally, it is crucial to assess any possible side effects and interactions with antidiabetic drugs.
Keywords: mechanism of action